The New Face of Ethnobotany: Tradition Meets Scientific Method - Yebouk, Cheikh (Ethnobotany Research and Applications, 2025)
Today, ethnobotany and ethnopharmacology bridge ancestral knowledge of traditional curative and therapeutic practices with current scientific understanding. Ethnobotany has undergone significant transformation over the past several decades. It has evolved from primarily documenting traditional medicinal uses, vernacular names, and plant-based activities to a multidisciplinary, hypothesis-driven field. Modern ethnobotany now serves as a vital bridge between traditional knowledge and modern scientific methodologies. This editorial examines the impact of these developments on ethnobotanical research and discusses the likely future direction of the discipline.